Polish patients use Google as a source of information on medication recalls on the example of drugs containing valsartan - a Google Trends analysis. - Damian Świeczkowski; Szymon Zdanowski; Piotr Merks; Miłosz Jaguszewski (Polish Pharmaceutical Society, 2019)
Background In addition to community pharmacies, the Internet has become an important source of information about medicines for patients, including medication recalls on the example of drugs containing valsartan. Aim The aim of the study was to verify a hypothesis that the frequency of specific Google searches in Polish increased during the periods of large scale valsartan recalls form the market which occurred between July 1st, 2018 and September 22nd 2019. Such increase would indicate that Google search engine is used by patients as a tool to seek information about withdrawn and recalled drugs. Material and methods Google Trends was used to obtain data on the relative frequency of searches of specific phrases connected to the topic. Four two-week periods, when valsartan formulations were being withdrawn from the Polish market, were identified and Poisson test was used to analyze the relative frequencies between those specified periods and the rest of the analysed timespan. All analyses were performed in R 3.5.3. P-values less than 0.05 were considered statistically significant. The results are reported with 95% CI. Results The relative frequency of searches including the phrase "walsartan wycofany" (eng. valsartran recalled) during the periods of the drug recalls was λ1 = 1,69 [1,56 - 1,83] while outside those periods it equalled λ2 = 0,52 [0,48 - 0,56]. For the second analysed phrase - "dyrektywa fałszywkowa" (ang. Falsified Medicine Directives) the values wereλ1 = 6,33 [6,07 - 6,58] and λ2 = 3,15 [3,06 - 3,25], respectively. In both cases the difference was statistically significant with p < 0,001. Conclusions During the periods of withdrawal and recall from the market of specific formulations containing valsartan and significant increase in the frequency of Google queries connected to the topic was registered. It may indicate that Google search engine, and more generally the Internet, is a significant source of information for Polish patients during periods in which medicinal products are being recalled. To fully appreciate the scope and the nature of the phenomenon, further quantitative and qualitative research is needed.